2018
DOI: 10.1155/2018/6272793
|View full text |Cite
|
Sign up to set email alerts
|

OperaBLE: An IoT-Based Wearable to Improve Efficiency and Smart Worker Care Services in Industry 4.0

Abstract: Industry 4.0 is leading the Fourth Industrial Revolution transforming traditional factories into smart factories governed by the Internet of Things (IoT). In order to assist smart factory employees, this paper introduces OperaBLE, a Bluetooth Low Energy (BLE) wearable proposal which is aimed at enhancing working conditions and efficiency in Industry 4.0 scenarios. We have developed two innovative algorithms for OperaBLE focused on power awareness as the key-enabling attribute towards success: Low-Frequency Mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Another interesting perspective to be considered is that wearable devices, such as smart watches [88] and smart wristbands, can be useful for estimating the operator's well-being (i.e., cognitive, psychological, and physical needs) in Human Cyber-Physical Systems (H-CPS) [93]. Wearable monitoring provides opportunities for health diagnostics and operator well-being in industrial environments, as was also identified in [94,95].…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting perspective to be considered is that wearable devices, such as smart watches [88] and smart wristbands, can be useful for estimating the operator's well-being (i.e., cognitive, psychological, and physical needs) in Human Cyber-Physical Systems (H-CPS) [93]. Wearable monitoring provides opportunities for health diagnostics and operator well-being in industrial environments, as was also identified in [94,95].…”
Section: Discussionmentioning
confidence: 99%
“…Birkel et al [30] put forward a reference framework of the risks involved in implementing I4.0 into SMEs with a sustainability approach, i.e., environmental, social, and economic risks, as well as technical risks, risks with information technologies and legal/political risks. Roda-Sánchez et al [31] proposed two power-aware algorithms with a flexibility approach to face the sustainability challenge in I4.0 (efficiency and working conditions). Ardanza et al [32] presented a human-machine interface with efficient sustainable hardware/software for I4.0.…”
Section: Taxonomymentioning
confidence: 99%
“…• Create new products/services as a result of the connectivity's interaction in the SCM: the interaction that is brought about by connectivity should contribute to creating innovative products and services by means of SCM. For instance, the interplay between IoT-wearable operations, an example of connectivity, is crucial to provide smarter worker care services [37].…”
Section: Innovativementioning
confidence: 99%